The importance of school culture in supporting student mental health in secondary schools. Insights from a qualitative study - Barker, Rhiannon; Hartwell, Greg; Egan, Matt; Lock, Karen (British Educational Research Journal, 2023)
Schools have the potential to provide a place of education and sanctuary for children and young people of all backgrounds. The rise in mental health problems in children and young people in the wake of the COVID-19 pandemic, particularly in relation to growing inequities, means that identifying ways in which schools can help respond to this growing mental health crisis demands urgent attention. This paper reports on case studies carried out in two London comprehensive schools, exploring how aspects of school culture impact (both positively and negatively) on student mental health. Methods comprised in-depth interviews with school staff and parents, focus groups with students and documentary analysis of relevant materials. Fieldwork was conducted during spring 2021 as schools were returning to face-to-face learning following national periods of lockdown. Our study shows how schools might attempt to drive positive mental health outcomes through aspects of school culture and uses a system framework to explore complexities around cause and effect in this area. Key findings include the considerable differences in school mental health provision, challenges in the identification of student mental health needs and the importance of recognising how the mental health of teachers must be considered alongside that of students. Overall, we highlight particular dilemmas of the post-lockdown era that our findings indicate for the education sector, and suggest there may be value in reframing the apparent conflict between ‘attainment gaps’ and personal development, moving towards an educational approach with greater complementarity of these aims.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/berj.3853
Keywords: children and young people; mental health; qualitative; research; school culture